11‐2: Technology Developments in High‐Resolution FMM‐free OLED and BEOL IGZO TFTs for Power‐Efficient Microdisplays. Issue 1 (28th June 2021) - Ke, Tung-Huei; Glushkova, Anastasia; Sandeheng, Calvin Mona; Alvarez, Gema Molina; Vandenplas, Erwin; Ciarnain, Rossa Mac; Malinowski, Pawel E.; Mitard, Jerome; Rassoul, Nouredine; Belmonte, Attilio; Tokei, Zsolt; Kar, Gouri Sankar; et al.
Abstract : Resolution, power efficiency, and brightness are crucial features in microdisplays for upcoming VR and AR applications. This presentation shows our work towards a high‐resolution direct RGB microdisplay. An IGZO TFTs with a top gate length of 80 nm is realized with 300mm facilities for high‐resolution backplane developments. For the development of high‐resolution OLED enabled by photolithographic patterning, we investigate an excess driving voltage in photolithographic patterned OLEDs caused by contaminants at the organic semiconductor interface. With necessary mitigation, we reduce the excess driving voltage and observe no significant lifetime change after multiple photolithographic patterning steps.